Adsorption and Kinetic Studies of Dyeing Clitoria ternatea L. Natural Dye onto Bamboo Yarn - Tengku Khamanur Azma, Tg. Mohd Zamri; Mimi Sakinah, A. M.; Zularisam, A. W. (Penerbit Universiti Malaysia Pahang, 2017)
In the present study, the bamboo yarn is dyed with a natural dye extracted from Clitoria ternatea L.flower. The effect of adsorption mechanism on the dyeing Clitoria ternatea L. natural dyes onto bamboo yarn were investigated. It has been observed that the adsorption process of time in the range of 10-90 minutes, with maximum adsorption capacity at 60 th minutes.Assessment of the effect of time on dye adsorption showed an increase in adsorption capacity with increasing time, with maximum adsorption at 60 minutes. Pseudo-first order, Pseudo-second order, and Intraparticle diffusion equations were employed to investigate adsorption rates. Pseudo-first order model provided the best fit indicating physisorption. The equilibrium adsorption data were fitted to Langmuir, Freundlich, Temkin, and Dubinin Radushkevish isotherm models. Langmuir isotherm model agreed well with the experimental data having high regression coefficients for dyeing bamboo yarn with dye concentration at 0.12 g/mL. These findings suggest that the application of natural dye from Clitoria ternatea L.flower onto bamboo yarn which is a new resource of the natural fiber in the industry is a good approach to get the desired dyeing, adsorption, and kinetic property.